2014
DOI: 10.1016/j.apsusc.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doping on the modification of polycrystalline silicon by spontaneous reduction of diazonium salts

Abstract: International audienceThe chemical modification of doped polycrystalline silicon materials (N+, N++ and P++) and silicon (1 0 0) and (1 1 1) used as references is investigated by spontaneous reduction of diazonium salts. The effectiveness of the grafting process on all polySi surfaces is shown by AFM and XPS analyses. The effect of substrate doping on the efficiency of the electrografting process is compared by using the thicknesses of the deposited organic films. For a better accuracy, two methods are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It is evident from the results that irrespective of the type of substrate, thick aminophenyl layers can be obtained using Fe powder reducing agent in the solution of para ‐phenylenediamine and sodium nitrite for a reaction time of 180 min, and the layer thickness is similar (60–68 Å) for the three representative substrates used in this experiment (Si, TiN, and Cu). The p‐doped single crystal Si surface with (100) orientation has been found to be the least reactive surface among various Si‐based substrates (N‐doped, polycrystalline Si,…) toward reducing diazonium cations from solution . Moreover in our case, the native oxide was not removed off Si, which makes the Si surface insulating.…”
Section: Methodsmentioning
confidence: 63%
“…It is evident from the results that irrespective of the type of substrate, thick aminophenyl layers can be obtained using Fe powder reducing agent in the solution of para ‐phenylenediamine and sodium nitrite for a reaction time of 180 min, and the layer thickness is similar (60–68 Å) for the three representative substrates used in this experiment (Si, TiN, and Cu). The p‐doped single crystal Si surface with (100) orientation has been found to be the least reactive surface among various Si‐based substrates (N‐doped, polycrystalline Si,…) toward reducing diazonium cations from solution . Moreover in our case, the native oxide was not removed off Si, which makes the Si surface insulating.…”
Section: Methodsmentioning
confidence: 63%
“…In recent years, there have been many studies on modified films on silicon wafers. Copper is also a commonly used metal in the electronics industry, so it is not only limited to the preparation of high-performance insulating films on the silicon surface but also of great significance to preparing insulating films on copper. Studies have shown that the addition of POSS to the polymer can make the material have high thermal stability, mechanical toughness, and oxidation resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Since control experiments showed no reaction between any of the organochalcogenide reagents tested in absence of the BBD initiator under these conditions, consideration of the mechanism starts with the reactivity of BBD with porous silicon, as shown in Figure a. As an electrophilic diazonium reagent, BBD is reduced by the silicon, leading to decomposition and formation of a bromoaryl radical and release of N 2 . , The resulting positive charge on the silicon surface may be neutralized via release of HBF 4 and formation of a surface Si radical. , Since the starting point of the reaction appears to be a surface-bound Si• group, the molecular chemistry of organochalcogenides with silyl radicals should lead to mechanistic insights. Molecules containing S- and Se- based substituents are well-established players in radical chemistry, including the molecular chemistry of silyl radicals. ,, A summary of representative radical reactions used to buttress the proposed surface-based mechanisms is shown in Table .…”
Section: Discussionmentioning
confidence: 99%
“…66,68 The resulting positive charge on the silicon surface may be neutralized via release of HBF 4 and formation of a surface Si radical. 66,74 Since the starting point of the reaction appears to be a surface-bound Si• group, the molecular chemistry of organochalcogenides with silyl radicals should lead to mechanistic insights. Molecules containing S-75−77 and Se-78−80 based substituents are well-established players in radical chemistry, including the molecular chemistry of silyl radicals.…”
Section: ■ Discussionmentioning
confidence: 99%